ADAT DAN PERUBAHAN BUDAYA PADA MASYARAKAT DAYAK KANAYATN - Hartatik, nfn (Balai Arkeologi Kalimantan Selatan, 2006)
The Dayak Kanayatn is still bounded by their indigenous tradition although they have converted into Catholicism and Christianity. Their indigenous tradition generally deals with aspects of custom of death and life. The custom of death Comprising mortuary rituals have gradually been abandoned and replaced by the Catholicism and Christianity funeral methods. Such abandonment is evident by the end of ritual of establishing traditional statues such as JlE.l11E.k (notokng pantak). On the other hand, the custom of life, which consist of rituals of birth, marriage, medicine and harvest worshipping, still persist and have been carried out at sacred places such as panvugu, pabuisan, padage, and paburungan. The Dayak Kanayatn visits these sacred places to pay respect and present offerings to Jubata. Such offerings are buah tangah, which consist of balanga (earthen jar) and bowls of rice and turmeric as well as nibbles of sticky rice and slaughtered-to-be chickens and pigs; these offerings are presented in attempt to ward off any kind of misfortunes. Traces of balanga and bowls are found scattered on the scared places besides wooden or stone posts signifying their sacredness.